Applying Pesticides in Compliance with the National Pollutant Discharge Elimination System (NPDES) - Frederick M. Fishel (EDIS)
On October 31, 2011, EPA issued a final National Pollutant Discharge Elimination System (NPDES) Pesticide Generic Permit for point source discharges from the application of pesticides to waters of the United States. This 10-page fact sheet explains what is now required for pesticide applications in Florida. Written by F.M. Fishel, and published by the UF Department of Agronomy, December 2011.